Federal Rules of Evidence - Legal Information Institute; Open Textbook Library (Open Textbook Library, 2016)
These are the Federal Rules of Evidence (FRE) as effective December 01, 2016. The FRE govern the introduction of evidence in civil and criminal trials in United States federal courts. These Rules are often the foundation for the standard upper level law school course in Evidence.
Article 1. General Provisions -- Article 2. Judicial Notice -- Article 3. Presumptions in Civil Cases -- Article 4. Relevance and Its Limits -- Article 5. Privileges -- Article 6. Witnesses -- Article 7. Opinions and Expert Testimony -- Article 8. Hearsay -- Article 9. Authentication and Identification -- Article 10. Contents of Writings, Recordings, and Photographs -- Article 11. Miscellaneous Rules
In English.
Description based on print resource
Keywords: Law -- Textbooks -- United States; Procedural Law -- Textbooks